7 - L'Union africaine comme réponse africaine au défi de la mondialisation: DOI: 10.4314/ad.v30i1.22216 - Kouam, Reine Djuidje (Africa Development, 2005)
This study deals with the construction of regional integretion as a tool for Africa to better adapt to globalisation. It analyses the African Union, from the perspective of the most recent African initiatives and strategies, created as a response to the new stakes brought about by globalisation. It questions whether the African Union (AU) is an appropriate response to the globalisation process, the key paradigms of which are integration and interdependence? In other words, is the fact of creating an institution enough to provide the African continent with the necessary means to challenge the problems brought about by globalisation, within today's world dispensation? The study attempts to present the pragmatic nature of the AU, bearing in mind that globalisation-related issues as well as the new elements in international relations as seen through an African perspective. It argues that this understanding implies an analysis of both the global and continental context of the AU creation, as well as its implementation processes, and objectives of its founders.